(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
In this article, we consider the field of comics as a research object of linguistics, how the unique features and structures of the medium provide rich opportunities for linguistic analysis and research, and by in-depth study of the nuances of speech, we will make it a research object of linguistics. we will study the importance of comics as an act